2014
DOI: 10.1007/s11356-014-3257-1
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and antigenotoxic potential of grape juice concentrate in blood and liver of rats exposed to cadmium

Abstract: The aim of this study was to evaluate the antimutagenic and antigenotoxic potential of grape juice concentrate in rodent organs exposed to cadmium chloride intoxication. A total of 15 Wistar rats were distributed into three groups (n = 5), as follows: control group (CTRL; nontreated group), cadmium group (Cd), and cadmium-grape juice group (Cd + GJ). Exposed animals received intraperitoneal injection of cadmium chloride (1.2 mg/kg body weight) diluted in water and, after 15 days, Cd + GJ group received grape j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
2
15
0
1
Order By: Relevance
“…These assays are widely employed to detect the genotoxicity of xenobiotics as a result of DNA strand breaks that could be induced by oxidative stress [36,37]. According to Tapisso et al [38], the presence of cadmium is related with increased frequencies of micronucleus and, even at low concentrations, is capable to induce DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…These assays are widely employed to detect the genotoxicity of xenobiotics as a result of DNA strand breaks that could be induced by oxidative stress [36,37]. According to Tapisso et al [38], the presence of cadmium is related with increased frequencies of micronucleus and, even at low concentrations, is capable to induce DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…mg/kg body weight) when assayed by single cell gel (comet) and micronucleus assays indicated decreased genotoxic effects in peripheral blood and liver cells [115]. Also a decrease in anti-8-hydroxy-20-deoxyguanosine (8-OHdG) expression level in hepatocytes was observed.…”
Section: Gautam Et Almentioning
confidence: 96%
“…It was shown that the administration of grape juice concentrate (polyphenols 1.18 mg/kg bw) for 15 days just 15 days after a single CdCl 2 i.p. injection (1.2 mg/kg bw) to rats, prevented hepatic DNA damage, which was reflected by a decrease in the level of 8‐hydroxy‐2′‐deoxyguanosine immunoexpression and enhanced the antioxidative capacity of liver cells by increasing the expression of Cu,Zn‐dependent SOD (de Moura et al, ).…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
“…The cross-over, placebo-controlled, investigation on overweight humans has shown that consumption of citrus limon glucoside (250 mg per drink, 2 drinks a day) lowered the serum concentration of the liver marker enzymes (ALT, ALP and GGT) and complement component C3 (protein of immune system playing a key function in activation of the complement system); therefore, it is hypothesized that this compound may be effective in the prevention and treatment of NAFLD, liver cancer, as well as diabetes and metabolic syndrome(Kelley et al, 2015). Investigations on animal models have demonstrated that citrus extracts alleviated this xenobioticinduced damage to the brain, bones and blood(de Moura et al, 2014;El-Tarras, Attia, Soliman, El Awady, & Amin, 2016;Ruiz et al, 2018) and indicated that the antioxidative potential of citrus may be used in protection of the liver against the toxic action of Cd(de Moura et al, 2014;Lakshmi et al, 2014;Renugadevi & Prabu, 2010).In the study byLakshmi et al (2014), the consumption of black grapes extract (400 mg/kg bw) during a 4 week exposure to Cd (as CdCl 2 , 5 mg/kg bw p.o.) significantly ameliorated rat hepatocyte damage caused by this element.…”
mentioning
confidence: 99%